The Deptford Trology: Fifth Business; The Manticore; World of Wonders - Davies, Robertson (Penguin Group, 1983)
Who killed Boy Staunton? Around the mystery of Boy Staunton's death, Robertson Davies weaves a glittering, fantastical, cunningly contrived trilogy of novels. Luring the reader down the labyrinthine tunnels of myth, history, and magic, The Deaptford Trology provides an exhilarating antidote to a world where ''the fear and dread and splendour of wonder have been banished.''
Keywords: Fiction